Non-Steroidal Anti-Inflammatory Drugs Prescribing in Patient with Gastrointestinal Risk - Aryanto Basuki; Sumaryono Sumaryono; Bambang Setyohadi; Armen Muchtar; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2006)
Conventional NSAID treatment has been consistently associated with gastrointestinal complications including dyspepsia syndrome, gastric ulcer, and upper gastrointestinal tract bleeding. There are some risk factors correlated to these complications, i.e. elderly age, previous history of gastric ulcer, concomitant use with steroid, multiple NSAID administration, high-dose NSAID and concomitant use with anticoagulant. NSAID prescribing with consideration of patient’s risk factor is necessary in order to decrease gastrointestinal complications. Combination therapy of NSAID and mucoprotector agent may be considered to prevent or to treat the NSAID- induced gastrointestinal ulcer Keywords: prescribing, NSAID, gastrointestinal risk